SEMANTIC MAPPING STRATEGY FOR STUDENTS WRITING SKILL - Nuraini, Hery; Kurniawan, Andri; Nissrina, Fanniar (JIPIS, 2022)
Writing became difficult for the 8th grade students at SMP Syekh-Yusuf Tangerang in achieving minimum criteria (KKM). It seemed that the teacher should overcome the problems. Semantic mapping strategy provides a good way to make students more active in practicing their skill in writing descriptive text. The aim of this study is to know the effect of semantic mapping strategy in improving students’ writing skill on descriptive text. Quantitative method with pre-experimental design was applied in this study. The total participants were 30 students from 8th grade. Based on the Wilcoxon Signed Rank calculation, the result showed that the sig value of pre-test and post-test was 0.000 which is less than 0.05 (0.000 < 0.05). So, there is a significant effect of the use of semantic mapping strategy in improving students’ writing skill on descriptive text for the 8th grade students at SMP Syekh-Yusuf Tangerang. Keywords: quantitative method, semantic mapping strategy, writing skill